Romantic relationship satisfaction and phubbing: The role of loneliness and empathy - Zhan, Siqun; Shrestha, Silu; Zhong, Nian (Frontiers in Psychology, 2022)
This study investigated the effects of loneliness and empathy on romantic relationship satisfaction and phubbing. Loneliness played a mediating role in romantic relationship satisfaction and phubbing. The level of empathy moderated these mediating effects. 504 Chinese adults completed tests of romantic relationship satisfaction, phubbing, loneliness and empathy. The results showed that romantic relationship satisfaction was negatively correlated with phubbing. Loneliness mediated this process. Specifically, lower romantic relationship satisfaction led to more phubbing by increasing loneliness. Our study also showed that the mediating relationship was moderated by the level of empathy. To be more specific, the higher the level of empathy, the stronger the impact of romantic relationship satisfaction on loneliness, and the more phubbing individuals exhibited.